Healthy snacks : [Unitate didaktikoa - Lehen Hezkuntza] - Berritzegune Nagusia; Euskadi. Hezkuntza Saila (Bilbo : Berritzegune Nagusia)
This unit is aimed at students in their 5th year of Primary Education on thetopic of "Food and nutrition". It has been designed as a CLIL (Content andLearning Integrated Learning) unit as we expect our students to work both onthe English language, as well as on curricular contents such as food andnutrients, healthy habits and diets.
LMH, 5. maila
Keywords: Baliabide digitalak; Curriculumeko baliabideak; Eduki digital didaktikoak